Molecular Interactions in Atomically Precise Metal Nanoclusters - Qian, Jing; Yang, Zhucheng; Lyu, Jingkuan; Yao, Qiaofeng; Xie, Jianping (Precision Chemistry, 2024)
For nanochemistry, precise manipulation of nanoscale structures and the accompanying chemical properties at atomic precision is one of the greatest challenges today. The scientific community strives to develop and design customized nanomaterials, while molecular interactions often serve as key tools or probes for this atomically precise undertaking. In this Perspective, metal nanoclusters, especially gold nanoclusters, serve as a good platform for understanding such nanoscale interactions. These nanoclusters often have a core size of about 2 nm, a defined number of core metal atoms, and protecting ligands with known crystal structure. The atomically precise structure of metal nanoclusters allows us to discuss how the molecular interactions facilitate the systematic modification and functionalization of nanoclusters from their inner core, through the ligand shell, to the external assembly. Interestingly, the atomic packing structure of the nanocluster core can be affected by forces on the surface. After discussing the core structure, we examine various atomic-level strategies to enhance their photoluminescent quantum yield and improve nanoclusters’ catalytic performance. Beyond the single cluster level, various attractive or repulsive molecular interactions have been employed to engineer the self-assembly behavior and thus packing morphology of metal nanoclusters. The methodological and fundamental insights systemized in this review should be useful for customizing the cluster structure and assembly patterns at the atomic level.